Case report: prolonged durable clinical benefit and low toxicity from combination endocrine therapy in a patient with recurrent endometrial carcinoma - Cheng, Joyce M.; Gaillard, Stephanie; Beavis, Anna L.; Rushton, Tullia; Fader, Amanda N. (Frontiers in Oncology, 2023)
Endometrial carcinoma is the most common gynecologic cancer, with increasing incidence and mortality. Combination endocrine therapy comprised of tamoxifen and progestational agents has demonstrated promising results in treating recurrent disease. This case report describes the prolonged clinical benefit of treatment with tamoxifen and megestrol acetate in a woman with recurrent, metastatic endometrial endometrioid carcinoma positive for estrogen (ER) and progesterone receptors (PR).A 71-year-old gravida 1 para 1 woman presented with postmenopausal bleeding and vaginal discharge. Pelvic ultrasound and magnetic resonance imaging confirmed a 4.7 cm endometrial mass. The patient underwent a total laparoscopic hysterectomy, bilateral salpingooophorectomy, pelvic and para-aortic lymphadenectomy, and cystoscopy; pathology revealed a FIGO stage IA grade 1 ER/PR-positive endometroid endometrial adenocarcinoma. She continued under active surveillance for approximately 42 months until she experienced bone metastases in her pelvis, for which she received radiation therapy. Five months later, pulmonary metastases were detected, and she received six cycles of carboplatin and paclitaxel. She then started megestrol acetate and tamoxifen and has remained clinically stable with minimal side effects and reasonable quality of life for approximately 57 months.Our case suggests that combination endocrine therapy has the potential to provide substantial long-term clinical benefit in women with recurrent endometrial cancer and bone metastases, despite multiple prior treatments, allowing patients to experience stable disease and quality of life. In patients with recurrent endometrioid, ER/PR-positive disease, endocrine therapy alone or in combination with other targeted therapies are regimens that may be considered due to their low overall toxicity.